Regional specificity of the climatic evolution of soils in the southern part of eastern Europe in the second half of the Holocene - Chendev, Yu. G.; Lupo, A. R.; Lebedeva, M. G.; Borbukova, D. A. (Eurasian soil science, 2015)
The analysis of characteristic features of chernozems and chestnut soils of different ages that have been formed in the south of the East European Plain in the past 5000 years attests to the spatial and temporal heterogeneity of the rate and direction of pedogenetic processes, i.e., to the metachronous development of the soil cover. A linear zone of the retarded (before 3600–3200 years ago) and, then, enhanced development of the humus profiles of chernozems was found along the Voeikov climatic axis corresponding to the contact zone between cyclonic and anticyclonic weather conditions. It was concluded about the significant rise in the degree of atmospheric moistening of the territory took place at the end of the Subboreal–the beginning of the Subatlantic periods of the Holocene. This factor favored the more active growth of the humus profiles of chernozems in this zone in comparison with chernozems on adjacent territories.